Hyperelongate ornamental tail feathers in a new early Cretaceous enantiornithine bird - Alexander D. Clark; Jingmai K. O’Connor; Xiaoli Wang; Yan Wang; Stephen Pruett-Jones; Xiangyu Zhang; Xing Wang; Xiaoting Zheng; Zhonghe Zhou (PLoS ONE, 2026)
Bird diversity is reflected in the abundance and variety of extraordinary plumages. Some of these include elongate, ornamental tail feathers that are typically attributed to either intraspecific communication in monomorphic species or sexual selection in sexually-dimorphic ones. Enantiornithines (Aves: Ornithothoraces) were the most diverse group of birds during the Cretaceous. Importantly, some enantiornithine fossils preserve soft tissues, most often in the form of feathers surrounding the body. Unlike any living bird, many enantiornithine specimens lack tail feathers (rectrices) all together, with the tail region consisting entirely of contour feathers. However, when present, enantiornithine rectrices typically consist of a pair of elongate, ornamental feathers with unusually wide rachises, referred to as rachis-dominated feathers. Here we describe Plumadraco bankoorum gen. et sp. nov., a new bohaiornithid enantiornithine with a pair of exceptionally long rectrices. These tail feathers measure twice the individual’s body length, ending in proportionally small pennaceous rackets, thus adding to the growing diversity of these unusual feathers. The fine preservation of these tail feathers, in comparison to other enantiornithine rectrices, reveals previously unrecognized structural variation that hints at their potential function in courtship displays. Although ornamental feathers in enantiornithines are widely considered sexually dimorphic, determining the selection pressures that shaped them is difficult due primarily to limited soft tissue data. Enantiornithine rectrices are likely the result of an interplay between both sexual and naturally selective pressures, similar to the processes which produce analogous structures in birds today.